Perbaikan Beberapa Sifat Kimia Tanah Ultisol Dengan Pemberian Bokashi Bungkil Inti Sawit (BIS) Terhadap Pertumbuhan Bibit Kelapa Sawit - hema malini (Mulawarman University, 2019)
The purpose of this study was to improve some of the chemical properties of Ultisol soil by giving Palm oil bokashi and to determine the effect of the best bokashi doses for the growth of oil palm seedlings.This research was conducted for 6 months starting in June until December 2017. The research location was at Jl. Mount Lingai North Samarinda. The design used was a randomized block design consisting of nine treatments and three replications. The treatment consisted of (P0) 0 g bokashi polybag-1, (P1) 100 g bokashi polybag-1, (P2) 200 g bokashi polybag-1, (P3) 300 g bokashi polybag-1, (P4) 400 g bokashi polybag-1, (P5) 500 g bokashi polybag-1, (P6) 600 g bokashi polybag-1, (P7) 700 g bokashi polybag-1, (P8) 800 g bokashi polybag-1. Soil samples were composited, then analyzed in the laboratory with the parameters of soil pH, organic C, N and C/N ratio. Plant data analyzed were plant height, number of leaves, stem diameter and plant weight. If it is significant then the LSD test will be at the level of 5%. The results showed that bokashi administration could improve soil pH, organic C, N and C/N ratio on Ultisol soil. Giving Bokashi Palm kernel meal obtained a soil pH of 4.57; Organic C 7.48; N 0,420; C/N Ratio of 19.45 in Ultisol soil. The application of Bokashi Palm kernel meal at a dose of 800 g polybag-1 in treatment P8 showed a significant effect on leaf number and plant weight, a very significant effect on plant height and stem diameter. The average plant height is 85.77 cm; average number of leaves 12.67; stem diameter of 4.90 cm; plant weight of 3.07 kg.